The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1159/000471513
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatic Compression, But Not Exercise, Can Avoid Intradialytic Hypotension: A Randomized Trial

Abstract: Background: Conventional hemodialysis (HD) is associated with dialysis-induced hypotension (DIH) and ineffective phosphate removal. As the main source of extracellular fluid removed during HD are the legs, we sought to reduce DIH and increase phosphate removal by using cycling and pneumatic compression, which would potentially provide higher venous return, preserving central blood flow and also offering more phosphate to the dialyzer. Methods: We evaluated 21 patients in a randomized crossover fashion in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 28 publications
1
20
0
1
Order By: Relevance
“…Four studies reported data on ultrafiltration (Table ). There were no major differences in the UF that was archived in the control group compared to IPC in two crossover trials and also on the mean UF filtration from a case series study of four patients . Lastly on the study performed by Macaulay et al results were reported as UF tolerability, in which three patients were able to achieve significantly higher UF rates after IPC was started …”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Four studies reported data on ultrafiltration (Table ). There were no major differences in the UF that was archived in the control group compared to IPC in two crossover trials and also on the mean UF filtration from a case series study of four patients . Lastly on the study performed by Macaulay et al results were reported as UF tolerability, in which three patients were able to achieve significantly higher UF rates after IPC was started …”
Section: Resultsmentioning
confidence: 93%
“…Alvarez et al described changes in body water, differences between water composition were analyzed pre and post‐intervention with IPC, a value defined as delta total body water was reported, no significant difference was found between groups . On a different study performed by Tai et al, a significant increase in fluid removal after HD using IPC was reported (−2.6 L versus −2.3 L, P = 0.05) (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations